Flipbook-Based Science E-Modules with the CINQASE Model: A Literature Review on Critical Thinking and Learning Outcomes - Johana Aulina Rahmatin; Agus Abhi Purwoko; Moh. Makhrus (Current Educational Review, 2025)
This study aims to identify and analyze the development trends of flipbook-based science e-modules with the CINQASE learning model in terms of critical thinking skills to improve student learning outcomes in junior high schools. This research method is descriptive analytical. The data used in this study were obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. The research procedure uses the PRISMA guidelines. The data identified and analyzed are the types of publications, publication sources, and research titles on the development trends of flipbook-based science with the CINQASE learning model in terms of critical thinking skills to improve student learning outcomes in junior high schools. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that the research trend on the development of flipbook-based science with the CINQASE learning model in terms of critical thinking skills to improve student learning outcomes in junior high schools indexed by Google Scholar from 2015 to 2024 has increased significantly in 2023. However, in 2024 there was a decrease in the research trend on this matter. There are 268 edited books and articles related to the discussion of flipbook-based science development research with the CINQASE learning model reviewed from the perspective of critical thinking skills to improve student learning outcomes in junior high schools. Keywords that are often used in research on this matter are e-module, student, problem, and skill.